2005
DOI: 10.5424/srf/2005143-00948
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of forest ecophysiological research in the context of Mediterranean Basin

Abstract: The mediterranean-climate regions are linked to the presence of the unusual global conditions of cool rainy winters and warm dry summers. Thus, the common drought periods, frost nights, summer heat and fires and soil erosion disturb plants life. These regions have a global significance by their floristic richness. Nevertheless, these areas have been more heavily impacted by human activities than almost any other ecosystem. The foreseeable global change will most likely influence plant life, and the Mediterrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Future climate changes will be likely affected by further increases in mean temperature, frequency and severity of extreme droughts and hot extreme events [ 27 , 28 ], therefore the understanding of plant responses to the changing environment represents an important research challenge for the Mediterranean forest ecosystems [ 29 ]. Ecophysiology represents an important tool to understand how plants will respond to the changing environmental conditions through the examination of mechanisms driving the functioning, distribution, abundance, and productivity of tree species [ 30 ]. Our analysis revealed that ecophysiology is a stable and a well defined research topic in the Mediterranean forest research.…”
Section: Discussionmentioning
confidence: 99%
“…Future climate changes will be likely affected by further increases in mean temperature, frequency and severity of extreme droughts and hot extreme events [ 27 , 28 ], therefore the understanding of plant responses to the changing environment represents an important research challenge for the Mediterranean forest ecosystems [ 29 ]. Ecophysiology represents an important tool to understand how plants will respond to the changing environmental conditions through the examination of mechanisms driving the functioning, distribution, abundance, and productivity of tree species [ 30 ]. Our analysis revealed that ecophysiology is a stable and a well defined research topic in the Mediterranean forest research.…”
Section: Discussionmentioning
confidence: 99%
“…Mediterranean Basin ecosystems are disturbed by soil erosion, drought periods, night frost, summer heat and forest fires (Fernández and Tapias, 2005). In recent decades, climate change (higher aridity and longer drought periods) and its consequences, such as changes in fire dynamics, could induce a loss of vigor, productivity and alter reproductive dynamics, decreasing the ecosystem resilience (Moriondo et al, 2006;Schiller and Atzmon, 2009).…”
Section: Introductionmentioning
confidence: 99%